An Exploration of Food Insecurity, Poverty, Livelihood and Local Food Potentials in Kulon Progo Regency, Indonesia - Dodi Widiyanto (Forum Geografi, 2018)
Kulon Progo has been struggled to cope with the issues of poverty and food insecurity. The provincial and local governments pay a lot of attention to tackling these deprivation problems. The BKPP DIY developed a composite index which concluded that poverty is the primary cause of the deprivation. Therefore, this paper aims to explore the rural deprivation in Kulon Progo by assessing its aspects including poverty, food insecurity conditions, livelihoods, and local food potentials. Several methods, including typology, livelihood calculation, and resource possibility mapping are introduced for the preliminary analysis of this deprivation. The findings show that in Kulon Progo, (1) most of the deprived areas are located in the typology of upland region, (2) based on its of five assets, in general, the livelihood condition in Kulon Progo needs an improvement on financial, natural, and physical capitals, and (3) presenting the local food clusters based on its local food plantation area and production, so that these findings could give alternatives for the decision makers to develop the rural (deprived) areas.